Digital Learning Media Social To Solve Their Difficulties In Writing Recount Text: Instagram Caption - Mohamad Sudi; Ferly Aninditya; Muhammad Ikra; Mutiara Indah; Bambang Ismaya (Jurnal Amal Pendidikan, 2023)
The use of social media platforms by students is growing rapidly. Therefore, teachers can capitalize on the growing interest in using social media in the classroom as its popularity among students continues to rise. Instagram is a very famous social media site. This research will explain how Instagram can be utilized to teach secondary school students in the art of writing Recount texts. This research is based on a real factual issue regarding students' difficulties in writing recount texts at the high school level. This research examines the challenges students face when tasked with creating recount texts and then highlights Instagram as a possible solution. This research focuses on discussing students' difficulties in writing recount texts and then presents Instagram as a solution to the students' difficulties. In answering the research question, the researcher used a qualitative approach with a Narrative Inquiry design in obtaining data that has been analyzed using the interactive model as the concept. This study found the results of students' difficulties in writing recount texts which include vocabulary, mechanics, grammar, content, and organization. The next result is that students can determine strategies in learning to write by writing status/caption on social media (Instagram) using English..